Pro-inflammatory cytokine and caspase-1 responses to pattern recognition receptor activation of neutrophils and dendritic cells in Behcet's disease - MUMCU, GONCA; DİRESKENELİ, RAFİ HANER (OXFORD UNIV PRESS, 2013)
Objective. Activated innate immunity is implicated in the pathogenesis of Behcet's disease (BD). To clarify the mechanisms of innate immune responses, we investigated inflammasome activation in dendritic cells (DCs) and neutrophils, following stimulation with two different pattern recognition receptors (PRRs) RIG-1-like (RLR) and NOD-like (NLR) in patients with BD. Methods. Sixteen active BD patients with mucocutaneous lesions and 17 healthy controls (HCs) were included in this study. DCs were generated from monocytes. DCs and isolated neutrophils were activated by RLR and NLR ligands. Caspase-1 activation and expression of p38 and RIP2 were determined by flow cytometry. Levels of IL-1 beta, IL-6, TNF-alpha, IFN-alpha and IL-18 in culture supernatants were measured by ELISA. Results. Activation of caspase-1 following intracellular PRR stimulation was found to be of similar levels in DCs and neutrophils of BD patients compared with HCs. However, activation of DCs from BD patients to NOD2 stimulus measured by the expression of RIP2 and p38 as well as IL-18 levels was found to be slightly defective (P < 0.05). In neutrophil cultures, IL-6 levels were lower in response to all stimuli in patients with BD compared with HCs (P < 0.01). Conclusion. Inflammasome formation following stimulation with NOD1/NOD2 and RIG measured by caspase-1 activation, cytokine levels and expression of RIP2 and p38 seems to be functionally normal in DCs and neutrophils of BD patients, although slightly defective responses in some pathways and cytokine levels were observed. These results may suggest that caspase-1-independent pathways such as toll-like receptors may be more prominent in BD pathogenesis.
Keywords: Behcet's disease; dendritic cells; inflammasome; neutrophils; pattern recognition receptors; INFECTIOUS ETIOLOGY; INNATE IMMUNITY; MANIFESTATIONS; PATHOGENESIS; ASSOCIATION; EXPRESSION; NOD2